Model Strategi Public Relations Humas Kota Bandung dalam Mempertahankan Citra Budaya Sunda - Destyra Rusmana; Atie Rachmiatie (Bandung Conference Series: Public Relations, 2023)
Abstract. The fading of Sundanese culture has had a major impact on the existence of culture in Indonesia. Each culture has an important role in shaping the national identity and cultural diversity of Indonesia. If Sundanese culture and other cultures continue to be marginalized and threatened with extinction, it will worsen the condition of cultural diversity in Indonesia and threaten the existence of culture as a part of national identity. The government's role in maintaining the existence of culture then becomes important. As an institution that relies on public trust, a positive image is a necessity. In building the positive image, of the role of public relations is needed. This research aims to find the role of the public relations strategy to maintain cultural image. The method used in this research is the qualitative method with the constructivism perspective and a case study of Bandung City Public Relations. Research results from this study are indicate that Bandung City Public Relations activities use existing aspects of the 4 Process PR model which consists of fact finding, planning, implementation and evaluation. Abstrak. Pudarnya budaya Sunda memiliki dampak yang besar pada eksistensi budaya di Indonesia. Setiap kebudayaan memiliki peran penting dalam membentuk identitas bangsa dan keberagaman budaya Indonesia. Jika budaya Sunda dan kebudayaan lainnya terus terpinggirkan dan terancam punah, maka akan memperparah kondisi keberagaman budaya di Indonesia dan mengancam eksistensi kebudayaan sebagai bagian dari identitas bangsa. Peran pemerintah dalam mempertahankan eksistensi budaya lantas menjadi penting. Sebagai lembaga yang mengandalkan kepercayaan publik, citra positif menjadi sebuah keharusan tersendiri. Dalam membangun citra peran public relations dibutuhkan secara utuh. Penelitian ini bertujuan untuk mengetahui bagaimana strategi public relations dalam mengemban tugasnya untuk menjaga citra budaya. Metode yang digunakan dalam penelitian ini adalah metode kualitatif dengan cara pandang konstruktivisme dan pendekatan studi kasus pada Humas Kota Bandung. Hasil pada penelitian ini menunjukkan kegiatan Humas Kota Bandung menggunakan aspek-aspek yang ada pada model 4 Process PR yang mana terdiri dari fact finding, planning, implementation dan evaluation